PENGARUH PENAMBAHAN HIDROLISAT TEMPE TERHADAP KUALITAS FISIK DAN KIMIAWI DARI PENYEDAP RASA - listyowati; tini, Rudiana Agus (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2024)
Flavoring is a food product additive that is used in food with the aim of adding flavor. The addition of flavorings can produce an umami taste in a dish. This research aims to make flavorings from shiitake mushrooms, beef and tempeh hydrolyzate. Tempeh protein is hydrolyzed with protease enzymes to produce tempeh hydrolyzate. The flavoring was tested proximately and the resulting water content was 7.3% - 11.53%, ash content 4.6 - 6.1% and protein content 33.44% - 43.55%. The research results indicated that formula 3 with the ratio (50 grams of shiitake mushrooms: 50 grams of beef: 20 grams of tempeh hydrolyzate) was preferred by respondents. Based on research, it shows that flavor enhancer from shiitake mushrooms, beef and tempeh hydrolyzate can be used as alternatives to synthetic flavorings.